A resilient cybersecurity framework for Mobile Financial Services (MFS). Issue 3 (1st October 2017) - Ambore, Stephen; Richardson, Christopher; Dogan, Huseyin; Apeh, Edward; Osselton, David
ABSTRACT: Cybercrime has astronomically risen with technological advancements alongside the business opportunities in cyberspace. Cybercrime is now viewed as one of the top 10 global risks. In recognition of the threat posed by cybercrime, organisations are investing in controls and countermeasures that would combat the threat of cybercrime and its impact. However, incidences of successful cyberattacks are still on the rise. The advent of mobile devices has created a means of providing financial services to over two billion people globally that hitherto had no access to formal banking services. Also, banks and other financial institutions use mobile platforms as an alternative delivery channel for financial services. However, the dark side of using mobile devices to bridge the banking gap is that mobile devices are now an added vector for cybersecurity threats. This has affected trust in the use of the system and consequently slowed down the uptake of mobile financial services (MFS). This article presents an in-depth analysis of the opportunities mobile platforms provide for the unbanked and how cybersecurity is hampering the uptake of MFS. Furthermore, the article proposes an approach for mitigating cybercrime in the complex MFS ecosystem and presents preliminary results from the research conducted so far.